A randomized phase III study comparing trastuzumab emtansine with trastuzumab, pertuzumab and docetaxel in elderly patients with advanced stage HER2-positive breast cancer: Japan Clinical Oncology Group Study (JCOG1607, HERB TEA study). (2nd July 2021) - Shimomura, Akihiko; Tamura, Kenji; Tanaka, Kiyo; Mizutani, Tomonori; Sasaki, Keita; Sekino, Yuta; Sawaki, Masataka; Shien, Tadahiko; Shibata, Taro; Iwata, Hiroji
Abstract: The standard first-line treatment for patients with human epidermal growth factor 2-positive metastatic breast cancer is a combination therapy of trastuzumab, pertuzumab and docetaxel, and the standard second-line treatment is trastuzumab emtansine. However, it may be difficult for the elderly to maintain sufficient intensity of treatment due to severe adverse events of trastuzumab, pertuzumab and docetaxel. The aim of this trial is to confirm the non-inferiority of trastuzumab emtansine over trastuzumab, pertuzumab and docetaxel in terms of overall survival in elderly (65-year-old or more) patients with human epidermal growth factor 2-positive metastatic breast cancer. If improved overall survival and fewer toxicities are observed, trastuzumab emtansine may be a feasible new standard first-line treatment for elderly patients with human epidermal growth factor 2-positive metastatic breast cancer. A planned total 330 patients will be enrolled from 45 institutions over 6.5 years. This trial has been registered in the UMIN Clinical Trials Registry as UMIN000030783 [http://www.umin.ac.jp/ctr/index.htm ]. Abstract : This is a randomized, multicenter, open-label, phase III trial to confirm non-inferiority of trastuzumab emtansine to trastuzumab, pertuzumab and docetaxel in terms of overall survival in older patients with human epidermal growth factor 2-positive, advanced breast cancer.